Developing advanced literacy in first and second languages : meaning with power - Schleppegrell, Mary.; Colombi, Cecilia (Mahwah, N.J. : Lawrence Erlbaum Associates, 2002)
This book addresses the linguistic challenges faced by diverse populations of students at the secondary and post-secondary levels as they engage in academic tasks requiring advanced levels of reading and writing. It aims to contribute to research and pedagogy on advanced literacy development.
Theory and practice in the development of advanced literacy / M. Cecilia Colombi and Mary J. Schleppegrell -- Multimedia semiotics: genres for science education and scientific literacy / Jay L. Lemke -- The development of abstraction in adolescence in subject English / Frances Christie -- Academic language development in Latino students' writing in Spanish / M. Cecilia Colombi -- Writing history: construing time and value in discourses of the past / James R. Martin -- Challenges of the science register for ESL students: errors and meaning-making / Mary J. Schleppegrell -- On the use of selected grammatical features in academic writing / Marianne Celce-Murcia -- Literacies, identities, and discourses / James Paul Gee -- African American language and literacy / John Baugh -- Enhancing the critical edge of (L2) teacher-education: some issues in advanced literacy / Vai Ramanathan -- Some key factors affecting English learners' development of advanced literacy / Robin Scarcella -- Writing to learn: science in the upper-elementary bilingual classroom / Barbara J. Merino and Lorie Hammond -- Writing backwards across languages: the inexpert English/Spanish biliteracy of uncertified bilingual teachers / Ofelia Garćia.
Includes papers presented at a conference held Feb. 2000, University of California, Davis.
Includes bibliographical references and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Literacy -- Study and teaching -- Congresses; Language and languages -- Study and teaching -- Congresses; Analphabétisme -- Étude et enseignement -- Congrès.; Langage et langues -- Étude et enseignement -- Congrès.; LANGUAGE ARTS & DISCIPLINES -- Literacy; Language and languages -- Study and teaching; Literacy -- Study and teaching; Leesvaardigheid; Conference papers and proceedings